Postlaparoscopic hysterectomy discharge within 24 h in Hospital Putrajaya: A feasibility study - Nurul Idayu Mohamad Padzil; Emily Christine D'silva; Anis Iryani Safiee; Wan Ahmad Hazim Wan Ghazali (Wolters Kluwer Medknow Publications, 2021)
Objective: The study objective was to determine the feasibility and selection criteria for discharge within 24 h posttotal laparoscopic hysterectomy with or without bilateral salpingo-oophorectomy (TLH with or without BSO) in Hospital Putrajaya. Materials and Methods: A total of thirty patients among all gynecology inpatients who were planned for TLH with or without BSO with controlled medical diseases, normal preoperative investigations, and uncomplicated surgery were recruited from January 2014 to December 2016. Data were collected from electronic medical records. Postoperatively, patients who fulfilled the selection criteria were discharged within 24 h and were followed up at 6 weeks and 3 months postsurgery. The results were presented as frequency with percentage and mean standard deviation. Results: All patients who had uncomplicated surgery and blood loss <1 l with no early postoperative complications were discharged within 24 h. They had a pain score of < 3 and were able to ambulate and tolerated orally well. None of these patients who were discharged 24 h postsurgery required readmissions. During follow-up, there were no reported complications such as persistent pain, wound infection, or herniation. Conclusion: Twenty-four hours' discharge post-TLH with or without BSO is feasible and safe if the selection process is adhered to.